Exploring Professional Wellbeing of English Language Teachers (Journal of NELTA, 2023)
Teacher wellbeing concerns teachers’ satisfaction, happiness, and attraction to their profession. It is equally essential in quality education since the attraction to English language in schools is growing gradually. This study aims to discovers perceptions of English language teachers teaching secondary level on their wellbeing in an institutional setting. Using lived stories through in-depth interview and informal communication, the study explores the perception of their wellbeing. The research findings show that teachers teaching English perceive their wellbeing as having positive psychology, positive emotion, respect and achievement in the job, and healthy relations among the institutional members. This study paves the way for a more extensive debate on policy and practice surrounding teachers’ wellbeing among educators, academicians, and decision-makers.